Sonates pour le pianoforte á deux mains: op. 57 - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Gustav Heinze; Leipzig; Germany, 2023)
Separate issue of the Piano sonata no. 23 in F minor, op. 57, published in Leipzig by Gustav Heinze as an "edition nouvelle et soigneusement revue," reprinted from the plates of Stern & Cie. in Berlin.